THE ROLE OF VISUAL ARTS IN BALANCING ADVERSE SITUATIONS IN INDIA - Upadhyaya, Alpana; wadhwa, Vinny (International Journal of Research -GRANTHAALAYAH, 2020)
Life has a strange way to unfold. Anything that exists on this Earth comes out of action, but the action only derives its fruits if it’s aligned with your inner world. Adverse situations in life will happen despite all the precautions and safeguards we put in place, in an attempt to prevent or at best avoid their effects. In this, people must concentrate on how to react and control the emotions in this situation. How to overcome negative thinking with the positive one? Positive thinking just means that you approach unpleasantness in a more positive and productive way. Visual Art can be a refuge for intense emotions and illness in adverse situations. Visual art draws people’s attention to details and the environment, which creates a distraction from day-to-day thoughts. No matter whether people chose visual arts to create for ourselves or simply observe or enjoy it.